CA19-9-producing esophageal adenocarcinoma originating from the esophageal cardia of the mid-thoracic esophagus: a case report - Naoki Kuwayama; Isamu Hoshino; Hisashi Gunji; Takeshi Kurosaki; Toru Tonooka; Hiroaki Soda; Itaru Sonoda; Ryotaro Eto; Nobuhiro Takiguchi; Yoshihiro Nabeya; Makiko Itami; Wataru Takayama (Surgical Case Reports)
Abstract Background Although there are many studies on primary esophageal adenocarcinoma arising from Barrett's esophagus or ectopic gastric mucosa, reports on adenocarcinoma arising from esophageal cardiac glands are extremely rare. Herein, we report a case of mid-thoracic cancer antigen 19-9 (CA 19-9)-producing primary esophageal adenocarcinoma, which presumably originated from the cardiac glands. Case presentation A 74-year-old man was referred to our department with advanced esophageal cancer, which initially presented with dyspepsia. Serum levels of cancer antigen 19-9 (CA 19-9) were elevated (724.89 U/ml). Upper gastrointestinal endoscopy revealed a type 2 tumor on the posterior wall of the mid-thoracic esophagus approximately 29–32 cm from the incisor. Mucosal biopsy was consistent with a diagnosis of adenocarcinoma. Contrast-enhanced computed tomography showed a circumferential wall thickening in the mid-thoracic esophagus without enlarged lymph nodes or distant metastasis. Positron emission tomography–computed tomography showed accumulation in the primary tumor, but no evidence of lymph node or distant metastasis. According to these findings, the adenocarcinoma was staged as cT3N0M0, thereby, requiring subtotal esophagectomy with lymph node dissection. Postoperative course was uneventful. Histopathologic analysis revealed a 50 × 40 mm moderately differentiated adenocarcinoma with invasion to the thoracic duct and lymph node metastasis at #108(1/4), #109R(1/3), and #109L(1/3). After surgery, the stage was revised to moderately differentiated pT4apN2pM0 (pStage III). Immunostaining revealed expression of CA19-9 and suggested esophageal cardiac gland origin of the tumor. Three months after the surgery, the patient showed no recurrence and is undergoing outpatient observation. Conclusions We experienced a case of mid-thoracic CA19-9-producing primary esophageal adenocarcinoma, which was presumed to have originated in the esophageal cardiac glands. Due to the scarcity of studies regarding this condition, specific management needs to be further clarified.